Evaluation of adjuvant activity of Astragaloside VII and its combination with different immunostimulating agents in Newcastle Disease vaccine. (April 2021) - Yakubogullari, Nilgun; Coven, Furkan Ozan; Cebi, Nusin; Coven, Fethiye; Coven, Nejdet; Genc, Rukan; Bedir, Erdal; Nalbantsoy, Ayse
Abstract: Astragaloside VII (AST-VII), a major cycloartane saponin isolated from Turkish Astragalus species, turned out to be one of the most active metabolites demonstrating Th1/Th2 balanced immune response. As Quillaja saponins are extensively used in adjuvant systems, this study made an attempt to improve AST-VII based adjuvant systems by using different immunostimulatory/delivery agents (monophosphoryllipid A (MPL), Astragalus polysaccharide (APS) and squalene) and to induce cellular and humoral immune response against a viral vaccine. For this purpose, Newcastle Disease vaccine (NDV) was chosen as a model vaccine. Swiss albino mice were immunized subcutaneously with LaSota vaccines in the presence/absence of AST-VII or developed adjuvant systems. AST-VII administration both in live/inactivated LaSota vaccines induced neutralizing and NDV specific IgG, IgG1 and IgG2b antibodies response as well as IL-2 and IL-4 production. APS based delivery systems enhanced the production of neutralizing antibody and the minor augmentation of IFN-γ and IL-2 levels. Squalene emulsion (SE) alone or combined with AST-VII were effective in NDV restimulated splenocyte proliferation. As a conclusion, AST-VII and AST-VII containing adjuvant systems demonstrated Th1/Th2 balanced antibody and cellular immune responses in NDV vaccines. Thus, these systems could be developed as vaccine adjuvants in viral vaccines as alternative to saponin-based adjuvants.